Melissopalynology: The Louveaux method on honey samples in the marche region and their allergenic potential - Nadia Trobiani; Silvia Bartolacci (Global Journal of Ecology - Peertechz Publications, 2022)
The research arises from the interest in investigating the pollen contained in the various honey samples analyzed to identify its geographical and botanical origin and to evaluate its allergenic potential. With the Louveaux method, the pollen content shall be observed under a microscope using the same procedure as the aerobiological analysis described in national and European standards. From the microscopic observation of the pollen grains, it is possible to identify the plants that produced them, thus going back to a particular type of vegetation that distinguishes the production area.  The percentage values for pollen of nectariferous plants identified have been calculated to establish frequency classes and dominant species. Starting from an exploratory analysis, the results obtained with melissopalynology provide assessments that, combined with sensory and physical analysis, represent a useful control tool to address the growing trend of food fraud as an element of consumer choice. By comparing the percentages of the pollen taxa contained in the honey analyzed with those reported in the characterization cards, it was possible to verify the conformity to the declared botanical origin. The samples were analyzed in duplicate to reduce operator uncertainty and to ensure the identification of the largest number of species/families present and the recognition of botanical families. The results provided a clear picture of a first assessment of the conformity of the reference values; in general, most of the samples examined, both those taken on the market and those of local producers, are in line with the data obtained. Bibliographical research on cross allergies related to the presence of pollen in honey has established that allergic forms to honey are still a rare condition and the incidence does not exceed 0.001%. Studying the few reported cases worldwide, it is difficult to say that pollen proteins are the only and directly responsible for the allergic manifestations that follow the ingestion of honey; however, if we wanted to attribute the responsibility, we could refer in particular to Compositae pollens, such as mugwort, ragweed, and dandelion. This work, while identifying many possible triggers for allergic reactions, has detected a very low number of cases of ingestion of honey; therefore, the study can be a starting point to investigate the allergenic potential.